Antimicrobial Application and Assessment of Green Synthesized Silver Nanoparticles Using Aqueous Leaf Extract of Ficus Copiosa - Timi, David; Gopalakrishnan, Subramaniyam; Maino, Macquin (British Journal of Healthcare and Medical Research, 2019)
Plant mediated green-synthesized silver nanoparticles (AgNPs) and the bioactivity on pathogenic micro-organisms is discussed. In the present investigation, aqueous leaf extracts of a medicinal plant, Ficus copiosa was utilized to construct AgNPs. The synthesized AgNPs was characterized by Ultraviolet-visible (UV-vis), Fourier Transform-infrared (FT-IR), X-ray Diffraction (XRD) spectrometer and Scanning Electron Microscopy (SEM) analysis. The phytosynthesized AgNPs exhibited comparable antimicrobial activity with two reference antibiotics against five indicator micro-organisms including two gram-positive (G+) bacteria, two gram-negative (G-) bacteria and a Protozoa (Pz). Study of the minimum inhibition concentration shows the two gram-negative bacteria to be more susceptible to AgNPs than the two gram-positive bacteria. The organisms included in the study are namely, B. Subtilis (G+), S. aureus (G+), E. coli (G-), S. pneumonia (G-) and T. vaginalis (Pz). Agar Disc diffusion technique was employed to assess the efficacy of the silver nanoparticles on the micro-organisms.